Application of Cement Kiln Dust as Activator of Ground Granulated Blast Slag for Developing A Novel Cold Mix Asphalt. Issue 1 (March 2021) - Al-Khafaji, Ruqayah; Dulaimi, Anmar; Sadique, Monower; Aljsane, Ayat
Abstract: The use of Cold bitumen emulsion mixtures (CBEMs) is associated with many issues which are the high air content, low strength at early ages and requiring long curing time as well as its high water sensitivity. This research aims to develop a new cold mix asphalt to be used as a binder course by utilising waste materials. So, ground granulated blast slag (GGBS) and cement kiln dust (CKD) were used as fillers in a polymer modified emulsion. GGBS was incorporated to replace the traditional fillers (limestone dust), meanwhile, CKD was used as an activator. Indirect tensile stiffness modulus (ITSM) was used to examine the mechanical characteristics and water sensitivity was measured via the stiffness modulus ratio (SMR). Meanwhile, the microstructure of the specimens was examined using scanning electron microscopy (SEM). The results indicated significant improvement in the mechanical properties as well as the water sensitivity with the incorporation of GGBS and CKD. These enhancements were confirmed by SEM which attributed that to the formation of hydration products at the early ages of specimens.